The development of a structural Model for adoption references of M-government services - Rashed Mohammed Alneyadi, Rashed Hamad (2022)
The The United Arab Emirates (UAE) is among the highest mobile phone subscribers in the world and its citizens prefer using mobile applications due to their ease of use, which makes mobile applications the most preferred tools in its smart government services. Therefore, this study was intended to develop and evaluate a structural model of adoption preferences of M-government services from the perspectives of UAE citizens with a view to understanding the preferences of adoption of m-government services in the UAE. The model is based on the relationship between six factors that can influence citizens' adoption preferences of m-government services, namely Social Influence (SI), Perceived Compatibility (PC), Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Trust in Technology (TT), and Perceived Risk (PR) with the Behavioural Intention to Adoption (BIA) and the National Culture (NC) as a mediator. This study has contributed to the body of knowledge on the development and assessment of model of adoption preferences of M-government services. Nonetheless, the UAE government is facing problems in increasing the level of citizens' adoption of M-government services. The two other relationships hypothesized between SI and PEOU and NC are negative; however, only one of them has significant effect on the NC, namely PEOU. Furthermore, it was found that the NC has no significant mediating effect on the relationship between the factors of adoption preferences of m-government services. Moreover, the study found that the NC has positive but not significant effect on BIA, highlighting the positive impact of the NC on citizens' adoption of m-government services. Unfortunately, there is little research that investigates this problem in the UAE. It is hoped that the findings from this study will help the authority to improve the m-government services in the UAE and similar contexts to encourage more citizens to use m-government services. To achieve the study objectives and to answer its questions, the data collected from 263 respondents via a survey working in public and private sectors in the UAE. Therefore, this study was intended to develop and evaluate a structural model of adoption preferences of M-government services from the perspectives of UAE citizens with a view to understanding the preferences of adoption of m-government services in the UAE. The data collected were analysed using SEM-AMOS software.